2015
DOI: 10.2147/ott.s84687
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of HOTAIR in four estrogen-dependent malignant tumors: a meta-analysis

Abstract: BackgroundHOX transcript antisense intergenic RNA (HOTAIR), a long non-coding RNA transcribed from the antisense strand of the HOXC gene locus, has been shown to be overexpressed in various carcinomas and is thought to be an indicator of poor prognosis. Recently, HOTAIR was found to be an estrogen-responsive gene. We therefore conducted a meta-analysis to systematically summarize and clarify the association between HOTAIR expression and prognosis in the four main estrogen-dependent tumors.MethodsA systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The incidence of lymph node metastasis was illustrated to be higher in cancer patients with high HOTAIR expression compared to patients with low HOTAIR expression (23). Likewise, HOTAIR was indicated to be a potential predictor of poor relapse-free survival, metastasis-free survival and disease-free survival in cervical, ovarian, breast and endometrial cancer patients (24).…”
Section: Discussionmentioning
confidence: 96%
“…The incidence of lymph node metastasis was illustrated to be higher in cancer patients with high HOTAIR expression compared to patients with low HOTAIR expression (23). Likewise, HOTAIR was indicated to be a potential predictor of poor relapse-free survival, metastasis-free survival and disease-free survival in cervical, ovarian, breast and endometrial cancer patients (24).…”
Section: Discussionmentioning
confidence: 96%
“…Predominantly, lncRNAs have been shown to regulate cancer cell viability, apoptosis, invasion and metastasis [ 28 - 34 ]. As is well-known, HOTAIR could regulate breast cancer proliferation and chemo-resistance as an oncogenic lncRNA [ 43 - 47 ]. Since the dysregulated lncRNAs between TNBC and adjacent normal tissues have been identified [ 35 , 36 ], there is still no information on the differentially expressed lncRNAs between TNBC and non-TNBC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HOTAIR and cervical cancer has also demonstrated that upregulation of HOTAIR promoted cervical carcinoma cells proliferation, invasion and migration [ 27 , 43 ]. In addition, in a meta-analysis containing eight eligible studies, zhang et al [ 44 ] showed that HOTAIR may be an indicator of poor prognosis in four main estrogen-dependent tumors, including cervical, ovarian, breast and endometrial cancers. The study of HOTAIR expression in the sera of cervical cancer patients indicate that the level of circulating HOTAIR may serve as a promising predicting and therapeutic target in cervical cancer[ 26 ].…”
Section: Discussionmentioning
confidence: 99%